2018
DOI: 10.1186/s12889-018-5638-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of the reliability and validity of the adolescent haze related knowledge awareness assessment scale (AHRKAAS)

Abstract: BackgroundHaze leads to many direct serious public health impacts. Understanding haze related knowledge can not only help adolescents organize health protection awareness to prevent the harmful effects that haze has on the body, but also promote their normal growth and development.MethodsBy considering, as the theoretical basis, the reasons behind the formation of haze and the underlying mechanisms of the diseases that it causes, in addition to also investigating extensive literature references, our research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Reliability and validity assessments are relatively easy to use and will result in better decisions when selecting or making recommendations for risk assessment tool use (Siedlecki & Albert, 2017). For the validity analysis, the I-CVI of this scale was 0.80 to 1.00, and the S-CVI was 0.91, indicating that the content validity was good (Dou et al, 2018). The KMO value was 0.694 and the Bartlett sphericity test value was 779.869 ( df = 55, p = .000), which showed the data were suitable for explorative factor analysis (Cicolini et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Reliability and validity assessments are relatively easy to use and will result in better decisions when selecting or making recommendations for risk assessment tool use (Siedlecki & Albert, 2017). For the validity analysis, the I-CVI of this scale was 0.80 to 1.00, and the S-CVI was 0.91, indicating that the content validity was good (Dou et al, 2018). The KMO value was 0.694 and the Bartlett sphericity test value was 779.869 ( df = 55, p = .000), which showed the data were suitable for explorative factor analysis (Cicolini et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The CVI of every item of the BARSHAS-SV indicates the number of expert choices of two and three divided by the total number of experts. The total CVI value of the BARSHAS-SV is the average value of all of items' CVI values (24). The CVI values revealed that the BARSHAS-SV was able to reflect the variables that researchers intended to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a tool that encompasses inquiries on air pollution sources, health effects, protective measures, attitudes, perceptions, and behavior was created. The questions were developed through a review and adaptation of items from previous studies [22,[30][31][32][33][34][35]. The instrument underwent validation by a group of public health experts and was tested in three schools before its finalization.…”
Section: Data Collection and Questions Askedmentioning
confidence: 99%